Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1590/acb360407
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin biopolymer sealant and aquatic exercise association for calcaneal tendon repair

Abstract: The aim of this work was to analyze the effect of fibrin biopolymer sealant (FS) associated or not to aquatic exercise (AE) on the calcaneal tendon repair. Methods: Forty-four female Wistar rats were randomly divided into four experimental groups: Lesion control (L), Lesion and FS (LS), Lesion and AE (LE) and Lesion and FS associated to AE (LSE). The edema volume (EV), collagen ratio, and histopathological analysis were evaluated after 7, 14, and 21 days of partial tendon transection. Results: The EV was stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Exercise has been shown to improve tendon wound healing by regulating tendon cell migration and proliferation. For instance, in a rat model, it was shown that aquatic exercise increased the proliferation of tenocytes in the calcaneal tendon following partial transection 38 . Similarly, treadmill running is known to increase tendon cell proliferation 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has been shown to improve tendon wound healing by regulating tendon cell migration and proliferation. For instance, in a rat model, it was shown that aquatic exercise increased the proliferation of tenocytes in the calcaneal tendon following partial transection 38 . Similarly, treadmill running is known to increase tendon cell proliferation 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies also evaluate “fibrin glues” that can be called fibrin adhesive, fibrin sealant or fibrin biopolymer in tissue regeneration [ 20 , 21 , 22 , 23 ]. Human fibrin glue is manufactured using two components, one of which is a concentrate of clotting proteins (fibrinogen, fibronectin and Factor XIII) and the other is thrombin, both lyophilized.…”
Section: Introductionmentioning
confidence: 99%